2019
DOI: 10.1016/j.ejor.2018.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Designing robust liner shipping schedules: Optimizing recovery actions and buffer times

Abstract: Abstractwritime trnsport is n importnt mode of trnsport in interntionl trdeF st is importnt for liner shipping ompnies to mintin ost e0ient nd roust liner shipping networksF egulrlyD they set up proEform shedulesD yet it is di0ult to sty on time nd we onsider the prolem to mnge the delysF hereforeD we need to determine n optiml reovery poliy nd u'er time distriution of the ship route in order to minimize the totl osts ssoited to delys nd reovery tionsD suh s inresing siling speedF e will introdue mixed integer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Eide et al ( 82 ) underlined that speed and load level of the ships highly impacted the routing determination. Mulder and Dekker ( 83 ) designed a liner shipping route to minimize operating costs.…”
Section: Discussionmentioning
confidence: 99%
“…Eide et al ( 82 ) underlined that speed and load level of the ships highly impacted the routing determination. Mulder and Dekker ( 83 ) designed a liner shipping route to minimize operating costs.…”
Section: Discussionmentioning
confidence: 99%
“…Mulder and Dekker [28] model the ship delay recovery problem as a Markov decision process to determine the optimal recovery policy and buffer time allocation by minimizing the total costs. Wen et al [29] study dynamic recovery policies for liner shipping service with the consideration of buffer time allocation and uncertainties.…”
Section: Liner Ship Scheduling Under Uncertaintymentioning
confidence: 99%
“…Moreover, findings of Li et al [39] suggested that adopting real-time disruption recovery policies helps reduce the costs incurred from uncertain port times. Mulder and Dekker [42] showed that another way to deal with port and sailing time uncertainties is buffer time allocation which can decrease costs around 28.9%.…”
Section: Uncertainty In Port and Sailing Timesmentioning
confidence: 99%